The role of mirror neurons in empathy, with a focus on their relevance in autism spectrum disorder and other clinical implications - Kiełt, Weronika; Kozłowska, Julia; Broniec, Gabriela; Wajdowicz, Barbara; Kudła, Aleksandra; Czapiewska, Rozalia; Dziewulska, Aleksandra; Wróbel, Aleksandra; Pacek, Laura; Kowalska, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction Mirror neurons are brain cells that engage when an individual performs an action and then observes another person completing the same action. These neurons are supposed to help us grasp others' emotions and intentions by mimicking their experiences. This has led to the theory that mirror neurons influence empathy, or the ability to share and understand the experiences of others. The article investigates the role of mirror neurons in empathy, specifically their potential contribution to emotional resonance, perspective-taking, their relevance in autism spectrum disorder and other clinical implications. Aim of the study The aim of this comprehensive review is to provide an overview of how mirror neurones contribute to the development and expression of empathy in humans, with a focus on their role in autism spectrum disorder. The objective of this research is to clarify the role of mirror neurons in social cognition and gain a better understanding of the neurological foundation for empathy. Materials and methods Scientific articles from the Pubmed, Google Scholar, and Web of Science databases were analysed. The goal of this study was to choose recent articles that most adequately encompassed the problems under consideration. The search was conducted out using the following keylords: mirror neurones, empathy and autism spectrum disorder. Summary Mirror neurones appear to play an important part in empathy, as evidenced by neural activity patterns during emotion identification. While they are not the single source of empathy or the only trigger, they are definitely present. Conflicting evidence limits our understanding of their exact impact, and more credible studies need to be conducted. However, current research reveals that mirror neurones have a measurable, although limited, impact on empathy.